2007
DOI: 10.1590/s1806-37132007000600011
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de um programa de alongamento muscular pelo método de Reeducação Postural Global sobre a força muscular respiratória e a mobilidade toracoabdominal de homens jovens sedentários

Abstract: Respiratory muscle stretching using the GPR method was efficient in promoting an increase in maximal respiratory pressures, thoracic expansion and abdominal mobility, suggesting that it could be used as a physiotherapy resource to develop respiratory muscle strength, thoracic expansion and abdominal mobility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
20

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 14 publications
(14 reference statements)
2
29
0
20
Order By: Relevance
“…The transverse abdomen increases the intra-abdominal pressure and stabilizes the spine. A satisfactory activation of this muscle by the volunteers may be associated with SP measurements, since they are related to the maintenance of expiratory air column pressure for phonation (4) . As a limitation of the study, the reduced number of subjects is highlighted, and considering that, in the literature studied, no similar studies were found, the discussions and inferences about the findings of this research become restricted.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The transverse abdomen increases the intra-abdominal pressure and stabilizes the spine. A satisfactory activation of this muscle by the volunteers may be associated with SP measurements, since they are related to the maintenance of expiratory air column pressure for phonation (4) . As a limitation of the study, the reduced number of subjects is highlighted, and considering that, in the literature studied, no similar studies were found, the discussions and inferences about the findings of this research become restricted.…”
Section: Discussionmentioning
confidence: 98%
“…The sound pressure (SP), measure that depends on complete glottic adduction and control of laryngeal movements is influenced by the increase in subglotal air pressure and expired airflow, as well as the maximum phonation times (MPT), which are related to support/duration of phonation and evaluate the coordination between levels of vocal production (2) . The muscle recruitment is essential for the maintenance of the respiratory system's mechanics that, under pathophysiological conditions in which muscle strength is altered, leads to a decrease in respiratory pressures, chest movement and subglotal air pressure (3,4,5) . Studies indicate that vocal production deficit may originate from respiratory capacity disorders, since this function is a source of energy for vocalization, especially in the expiratory phase (6,7) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, increased lumbar lordosis is often noted in these patients; this change may cause an associated imbalance of the muscular system that will inhibit normal movement. Interestingly, some investigators demonstrated that postural reeducation improves respiratory muscle strength and the ability to expand the rib cage in sedentary subjects 27 . The role of DLco in pulmonary function testing is to provide information on the transport of gas from alveolar air to hemoglobin 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Azeredo (24), em estudo que combinou os exercícios aeróbicos com alongamentos e exercícios ventilató-rios diafragmáticos, obteve resultados que favoreceram o reequilíbrio da musculatura inspiratória e expiratória minimizando as alterações decorrentes da debilidade muscular, estimulando a atividade diafragmática e, assim, promovendo aumento do VC. Outro estudo relacionado com a prática de exercí-cios globais associados aos exercícios respiratórios dentro de um programa de reabilitação por meio da reeducação postural global, no período de 8 semanas, em jovens saudáveis e sedentários, ocasionou melhora significativa nas pressões respiratórias má-ximas e na mobilidade tóraco-abdominal (25).…”
Section: Discussionunclassified